2002
DOI: 10.1177/001112802237128
|View full text |Cite
|
Sign up to set email alerts
|

Improving Juvenile Justice for Females: A Statewide Assessment in California

Abstract: This article reports findings from a survey of officials from various California state agencies and a series of interviews and focus groups with female youth and professionals serving this population. The study examined types of services provided, program barriers, and facilitation of change. The findings were used to make gender-specific policy and program recommendations. The authors found that meeting the needs of girls and young women requires specialized staffing and training, particularly in terms of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 10 publications
1
59
0
4
Order By: Relevance
“…Variables were selected based on theory (Bloom et al 2002;Covington and Bloom 2006;Zahn 2007) and previously identified empirical relevance (Holman and Ziedenberg 2006;Mallett 2009). To examine the influence of race, mental health disorders, and substance use disorders on select court outcomes of juvenile offenders for males and females, a series of multiple regression equations and logistic regression models were computed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables were selected based on theory (Bloom et al 2002;Covington and Bloom 2006;Zahn 2007) and previously identified empirical relevance (Holman and Ziedenberg 2006;Mallett 2009). To examine the influence of race, mental health disorders, and substance use disorders on select court outcomes of juvenile offenders for males and females, a series of multiple regression equations and logistic regression models were computed.…”
Section: Discussionmentioning
confidence: 99%
“…Gender-responsive perspectives start from the position that the experiences, needs, and strengths of males and females should be considered in the design and development of gender-responsive interventions because females and males respond differently to interventions (Bloom et al 2002;Covington and Bloom 2006). Gender responsive perspectives are based on the premise that similar risk factors appear to promote delinquency among male and female youth, but the level and rate of exposure and sensitivity to certain risk factors may differ across gender (Zahn 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Par ents have different expectations about their sons' and daughters' obedience to parental authority (Chesney-Lind, 1988), and these expectations may affect how the justice system responds to a girl's behavior when she "acts out" with in the home (Krause and McShane, 1994). Research indicates that girls fight with family members or siblings more frequently than boys, who more often fight with friends or strangers (Bloom et al, 2002). Some research suggests that girls are three times as likely as boys to assault a family member (Franke, Huynh-Hohnbaum, and Chung, 2002).…”
Section: Ratio Of Arrest Ratesmentioning
confidence: 99%
“…Una revisión de programas de experiencias exitosas referenciada por la Oficina de Justicia Juvenil y Prevención de la Delincuencia, describen que son 24 los programas que se refieren de forma específica a niños y sólo 2 a niñas (Howell, 2003). De los 62 programas descritos en un estudio efectuado por Bloom et al (2002), el programa más común era un programa de prevención de la delincuencia, seguida por el grupo de tratamiento e institucional. Casi todos fueron mixtos en un (77%) y sus usuarios/as eran mayormente varones hispanos, caucásicos/as y afroamericanos.…”
Section: El Programa Gemsunclassified
“…La programación eficaz orientada a las niñas y las mujeres debe ser moldeada y adaptada a sus situaciones y problemas reales. Sin embargo, Bloom et al (2002), señalaron que la dirección específica sobre cómo lograr estos objetivos no es fácilmente evidente a partir de la literatura existente. Los escasos programas eficaces para las niñas y las mujeres deben ser adaptados a su situación problemática y su realidad contextual.…”
Section: Pozo Vives and Orte -Prevención De Drogodependenciasunclassified